Lab Math : a handbook of measurements, calculations, and other quantitative skills for use at the bench - Adams, Dany Spencer (Cold Spring Harbor Laboratory Press, 2003)
Work at the biology bench requires an ever-increasing knowledge of mathematical methods and formulae. In Lab Math, Dany Spencer Adams has compiled the most common mathematical concepts and methods in molecular biology, and provided clear, straightforward guidance on their application to research investigations. Subjects range from basics such as scientific notation and measuring and making solutions, to more complex activities like quantifying and designing nucleic acids and analyzing protein activity. Tips on how to present mathematical data and statistical analysis are included. A reference section features useful tables, conversion charts and \"plug and chug\" equations for experimental procedures. This volume is an excellent, structured source of information that in many laboratories is often scattered and informally organized.Related Titles from the Publisher Statistics at the Bench: A Step-By-Step Handbook for Biologists Lab Dynamics At the Bench At the Helm Lab Ref, Volume 2: A Handbook of Recipes, Reagents, and Other Reference Tools for Use at the Bench
Keywords: Clinical Laboratory Techniques; přírodní vědy; chemie, klinická chemie; klinické laboratorní techniky; Mathematics; matematika